(untitled) (University Heart Journal, 2021)
Background: Insulin resistance is a well-established composite index of systemic inflammatory and metabolic disorders. A wide variety of methods like, HOMA-IR (Homeostatic model assessment insulin resistance), FGIR (Fasting glucose insulin ratio), ISI-Composite (an index of whole body insulin sensitivity), QUICKI (quantitative insulin sensitivity check index) etc are available for assessing IR. Objective: To find out the correlation between insulin resistance and LVEF in non diabetic chronic heart failure patients. Methodology: This cross sectional study was carried out in the Department of Cardiology in Bangabandhu Sheikh Mujib Medical University, Shahbagh, Dhaka from February, 2019 to June, 2020. Patients admitted with chronic heart failure with reduced ejection fraction were included in this study. Patients with diabetic, prediabetic and patient who did not give written informed consent were excluded in this study. Results: LVEF 25-29% was 16 patients out of which 10(66.7%) had significant insulin resistance. LVEF 30- 34% was found in 28 patients, among them 16(41.0%) had no insulin resistance. LVEF 35-39% was found in 19 patients out of which 18(46.2%) had no insulin resistance. The difference was statistically significant (p<0.05). A negative correlation (r=-0.340; p=0.006) was found between insulin resistance and LVEF. Conclusion: Majority non diabetic chronic heart failure patients had no insulin resistance. Significant negative correlation was found between insulin resistance and LVEF. University Heart Journal Vol. 17, No. 2, Jul 2021; 99-102